Ideas: A deep dive into the transatlantic slave trade - United Nations Educational, Scientific; Cultural Organization; Madick Gueye (The UNESCO Courier, 2024)
Off the coast of the island of Gorée – a symbol of human exploitation – African researchers are carrying out underwater explorations to locate and identify the wrecks of slave ships. Their mission is not only to document the history of the transatlantic slave trade, but also to approach it from a different perspective.